Case Report: Palliative radiotherapy monitoring using computed tomography and diffusion-weighted magnetic resonance imaging in a cat with ceruminous gland adenocarcinoma - Kim, Junyoung; Kim, Soyeon; Hong, Sunghwa; Kim, Eunjee; Yoon, Junghee; Choi, Jihye (Frontiers in Veterinary Science, 2025)
BackgroundCeruminous gland adenocarcinoma is the most common malignant tumor of the feline external ear canal. These tumors are often locally invasive and may extend into adjacent musculature and lymph nodes, limiting the feasibility of surgical excision. When surgery is not an option, radiation therapy can provide palliative benefit. Advanced imaging modalities, including computed tomography (CT) and magnetic resonance imaging (MRI), play a crucial role in treatment planning and therapeutic monitoring.Case descriptionA 14-year-old spayed female Persian cat with a confirmed diagnosis of ceruminous gland adenocarcinoma presented with a progressively enlarging mass in the left external ear canal. Due to extensive local invasion into the adjacent parotid and salivary regions, surgical resection was not feasible. The cat was treated with palliative-intent radiation therapy (36 Gy in 6 weekly fractions). Serial CT and MRI, including diffusion-weighted imaging (DWI) and apparent diffusion coefficient (ADC) mapping, were performed on days 0 (radiotherapy completion), 30, 90, and 180 to monitor treatment response. During the initial follow-up period, imaging demonstrated sustained tumor size reduction, symptomatic improvement, and minimal adverse effects. Functional MRI delineated residual lesions more clearly than conventional sequences, supporting its role in post-treatment assessment. However, on day 180, imaging revealed suspected local recurrence and regional lymph node metastases, suggesting disease progression. Despite this, the treatment successfully achieved the intended palliative goals, including temporary tumor control and clinical stabilization.ConclusionThis report described a rare case of feline ceruminous gland adenocarcinoma characterized by local invasiveness that precluded surgical resection. Palliative radiotherapy was administered, and sequential imaging using computed tomography and diffusion-weighted magnetic resonance imaging, including ADC mapping, enabled detailed monitoring of the tumor response. Although conventional imaging confirmed size reduction, DWI-MRI better delineated residual lesions, suggesting its complementary role in radiotherapy assessment. This case underscores the value of combining anatomic and functional imaging for evaluating radiotherapy outcomes and guiding clinical decision-making in feline oncology.